Predictors and prognostic significance of tachycardiomyopathy: insights from a cohort of 1269 patients undergoing atrial flutter ablation. (1st February 2016) - Brembilla‐Perrot, Béatrice; Ferreira, João Pedro; Manenti, Vladimir; Sellal, Jean Marc; Olivier, Arnaud; Villemin, Thibaut; Beurrier, Daniel; De Chillou, Christian; Louis, Pierre; Brembilla, Alice; Juillière, Yves; Girerd, Nicolas
Abstract: Background: Atrial flutter‐related tachycardiomyopathy (AFL‐TCM) is a rare and treatable cause of heart failure. Little is known about its epidemiology and long‐term prognosis. Our aims are to determine the prevalence, predictors and outcomes of AFL‐TCM. Methods and results: A total of 1269 patients were referred for radiofrequency ablation of AFL between January 1996 and September 2014; 184 had reduced left ventricular ejection fraction (LVEF <40%). At 6 months after AFL ablation, 103 patients (8.1% of the population, 56% of patients with baseline LVEF <40%) had marked LVEF improvement: these were considered to have AFL‐TCM. Patients with persisting reduced LVEF were considered to have systolic dysfunction unrelated to AFL. Patients were followed for a median (percentile25–75 ) of 1.15 (0.4–2.8) years. Patients with AFL‐TCM were younger, had lower prevalence of ischaemic cardiomyopathy and used less antiarrhythmic drugs than patients with systolic dysfunction unrelated to AFL. In multivariable analysis, ischemic cardiomyopathy [odds ratio (OR) = 0.32, 95% confidence interval (CI) 0.15–0.68) P  = 0.003] and prescription of antiarrhythmic drug before ablation [OR = 0.41, 95% CI 0.20–0.84, P  = 0.02] were significantly associated with a lower probability of LVEF improvement during follow‐up. Patients with AFL‐TCM had similar survival to patients without systolic dysfunction at baseline [hazard ratio (HR) = 0.96 95% CI 0.34–2.65, P  = 0.929], whereas patients with systolic dysfunction unrelated to AFL had higher mortality rates compared with patients without systolic dysfunction at baseline [HR = 2.88, 95% CI 1.45–5.72, P  = 0.002]. Conclusions: Marked LVEF improvement was observed in 56% of patients with baseline LVEF <40% at 6 months after ablation. These patients had similar survival to patients without baseline systolic dysfunction, whereas patients who remained with LVEF <40% had a threefold increase in mortality rates.